Malay Translation and Validation of Modified Checklist for Autism in Toddlers, Revised with Follow-up (M-CHAT-R/F) - R. A. Ariffin; J. Ismail; F. N. Abd Rahman; W.S. Wan Ismail; N. Ahmad; A. Abdul Ghafar; W.W. Yang (Frontiers in Pediatrics, 2025)
Indexed by ERA